MEMAHAMI KORUPSI DI DAERAH PASCA DESENTRALISASI: BELAJAR DARI EMPAT STUDI KASUS - Budi Setiyono (Program Magister Ilmu Politik, Universitas Diponegoro, 2017)
Since ‘reformasi movement’ and decentralization takes place, a lot of local government officials (politicians and bureaucrats) are jailed due to their involvement in corruption cases. While on the one hand, this may an evidence that corruption eradication efforts have shown positive results, but on the other hand, it leaves ironic heartbreaking questions. Why these officials caught in corruption cases? Are they economically shortage that forced them to illegally